Analysis of Total Effective Equipment Performance SD5 Machine on Krosok Production Line, Primary Manufacturing Department. (Case Study: PT NT) - Adhie Prayogo (Journal of Industrial Engineering and Technology, 2020)
PT NT is one of an International Tobacco Industries in Indonesia. The rapid development of the cigarette industry, as well as the increased demand, encourage many companies to evolve their production quality and capacity. One effort established by PT NT is controlling the effectiveness of production machines, including SD5 machine. In this study, an analysis of SD5 machine performance conducted using the Overall Equipment Effectiveness and Total Effective Equipment Performance. Based on the ten days of direct observation of machine performance, the study revealed that the OEE level was only a mere at 63.2%, under the world level, 85%. Further, the TEEP number was about 36.8%. Those low figures were mainly caused by the low level of machine utilization and availability. Thus, the fishbone diagram established to discover the main causal, reporting that four main aspects, human, methods, material and machine, played essential roles in the problem.